1996
DOI: 10.1007/bf00027485
|View full text |Cite
|
Sign up to set email alerts
|

Expression of barley yellow dwarf virus and Russian wheat aphid resistance genes in and fertility of spring wheat × triticale hybrids and backcross lines

Abstract: The Barley Yellow Dwarf Virus disease (BYDV) and the Russian wheat aphid (RWA) Diuraphis noxia (Mordvilko) have caused significant losses to wheat and barley in several areas of the world . Important sources of resistance to both BYDV and RWA have been found in Triticale . Different generations of interspecific wheat x Triticale crosses were produced and the progenies were screened for BYDV and RWA tolerance . Plants with equal chromosome numbers showed different levels of fertility. A significant correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Our primary aim in this work was to determine whether the background into which a factor for resistance to B. brassicae is introgressed influences the phenotypic expression of that resistance. Previous reports have indicated that the choice of 'genetic background' can influence the expression of resistance (Luig & Rajaram, 1972;Walkey et al, 1985;Nkongolo, 1996;Potgieter, Marais & Du Toit, 1991). In the present study we wanted to determine whether the choice of 'susceptible' parent influenced the expression of resistance to B. brassicae in the F2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our primary aim in this work was to determine whether the background into which a factor for resistance to B. brassicae is introgressed influences the phenotypic expression of that resistance. Previous reports have indicated that the choice of 'genetic background' can influence the expression of resistance (Luig & Rajaram, 1972;Walkey et al, 1985;Nkongolo, 1996;Potgieter, Marais & Du Toit, 1991). In the present study we wanted to determine whether the choice of 'susceptible' parent influenced the expression of resistance to B. brassicae in the F2.…”
Section: Discussionmentioning
confidence: 99%
“…Faster flowering B. oleracea genotypes exist and it was decided to attempt to transfer the resistance of the three kale accessions into a 'rapid flowering' background which would be more amenable for experimental studies. However, the choice of plant line, and therefore the genetic background, that disease and pest resistance is introduced into has been shown to influence the expression of resistance (Luig & Rajaram, 1972;Walkey, Ward & Phelps, 1985;Pretorious, Rijkenberg & Wilcoxson, 1990;Nkongolo, 1996;Warnock, Davis & Gingera, 1998). This paper reports the results of investigations into the influence of genetic background on resistance to B. brassicae derived from the cv.…”
Section: Introductionmentioning
confidence: 99%